Conhecimento dos internos do curso de medicina de uma universidade federal do interior do estado de Sergipe sobre protocolo de morte encefálica - Nardoto, Emanuella Maria Lopes (2019)
The term Brain Death (ME) is presented by the Ministry of Health (MS) as a complete and irreversible function of the neurological functions of the individual, as well as their clinical death. Transplantation Law - No. 9434 of February 4, 2007, delegates the Federal Medical Council (CFM) a responsibility to define the diagnostic criteria of ME for which they were instituted established by CFM Resolution 1480 of August 21, 1997 and last resolution by Resolution CFM No. 2173 of November 23, 2017. The latter resolution is cited for the need to open the Protocol of Brain Death, the patient must be in an apperceptive coma, without supraspinal reactivity and in persistent apnea. In addition, the prior needs of the disease known as irreversible and irrelevant and of known cause, the absence of treatable factors, treatment and hospital observation during the first hours and hemodynamic stability should be necessary. Firstly, it is necessary to follow the clinical examination, additional examination and the apnea test. The last transplant registry in 2017 is the second largest number of transplants, the largest number of transplants being effective. Still, Brazil is the next to pay by the end of 2017 a waiting line of 32,404 people. In Sergipe there were 108 in 2017 and only 7 transplants, which happened with 43 hospitals and 355 ICU beds and no liver, pancreas and lung transplantation. The need to study and debate on the subject is evidenced when several studies with different populations - laymen and non-laymen - are proof of the lack of information and insecurity about the MoE supporting and thus justifying a relevance of the debate about the same.